Metasurface: Enhancing gain of antenna and energy harvesting system design. Issue 2 (26th November 2019) - Liu, Ruipeng; Wang, Xia; Nie, Dong; Wang, Lu; Cui, Wenjie; Wang, Mengjun; Zheng, Hongxing; Li, Erping
Abstract: The metasurface technique has been applied to enhancing the gain and directivity of antenna in this paper. The normal metal ground is replaced by one metasurface structure to suppress the higher frequency component transmission. Another similar metasurface structure is put nearer to the antenna to increase gain and enhance directivity further. A low‐pass filter with defected ground plane is designed to obtain steeper falling edges and a wider stop band. Then a rectifier circuit is designed for the electromagnetic energy of input terminal converted into a DC output. The three parts of passive circuit make up a complete energy receiving system. The measured results of the system shown that the output voltage stable.